Supramolecular adhesive hydrogels for tissue engineering applications - Zhao, Yue (2022)
Tissue engineering is a promising and revolutionary strategy to treat patients who suffer the loss or failure of an organ or tissue, with the aim to restore the dysfunctional tissues and enhance life expectancy. Supramolecular adhesive hydrogels are emerging as appealing materials for tissue engineering applications owing to their favorable attributes such as tailorable structure, inherent flexibility, excellent biocompatibility, near-physiological environment, dynamic mechanical strength, and particularly attractive self-adhesiveness. In this review, the key design principles and various supramolecular strategies to construct adhesive hydrogels are comprehensively summarized. Thereafter, the recent research progress regarding their tissue engineering applications, including primarily dermal tissue repair, muscle tissue repair, bone tissue repair, neural tissue repair, vascular tissue repair, oral tissue repair, corneal tissue repair, cardiac tissue repair, fetal membrane repair, hepatic tissue repair, and gastric tissue repair, is systematically highlighted. Finally, the scientific challenges and the remaining opportunities are underlined to show a full picture of the supramolecular adhesive hydrogels. This review is expected to offer comparative views and critical insights to inspire more advanced studies on supramolecular adhesive hydrogels and pave the way for different fields even beyond tissue engineering applications.